2015
DOI: 10.1111/mmi.13000
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of reductases IruO and NtrA in iron acquisition by Staphylococcus aureus

Abstract: SummaryTo obtain host iron, Staphylococcus aureus secretes siderophores staphyloferrin A (SA) or staphyloferrin B (SB), and accesses heme iron through use of ironregulated surface determinant proteins. While iron transport in S. aureus is well documented, there is scant information about proteins required to access iron from complexes in the cytoplasm. In vitro studies identified a pyridine nucleotide-disulfide oxidoreductase, named IruO, as an electron donor for the heme monooxygenases IsdG and IsdI, promotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 88 publications
(148 reference statements)
0
20
0
2
Order By: Relevance
“…Haem is degraded by the haem monooxygenases IsdG and IsdI to release iron (Skaar et al, 2004a). Recently, Hannauer et al (2015) reported the involvement of two additional reductases, NrtA and IruO, in haem iron removal by Staphylococcus aureus. The Isd-mediated haem uptake system of Staphylococcus aureus was comprehensively reviewed by Hammer & Skaar (2011) and its significance in Staphylococcus aureus infections is demonstrated by its requirement for full virulence in several models of pathogenesis, as reviewed by Grigg et al (2010).…”
Section: Haem Uptake Systemsmentioning
confidence: 99%
“…Haem is degraded by the haem monooxygenases IsdG and IsdI to release iron (Skaar et al, 2004a). Recently, Hannauer et al (2015) reported the involvement of two additional reductases, NrtA and IruO, in haem iron removal by Staphylococcus aureus. The Isd-mediated haem uptake system of Staphylococcus aureus was comprehensively reviewed by Hammer & Skaar (2011) and its significance in Staphylococcus aureus infections is demonstrated by its requirement for full virulence in several models of pathogenesis, as reviewed by Grigg et al (2010).…”
Section: Haem Uptake Systemsmentioning
confidence: 99%
“…[25] Angesichts eines essentiellen, aber in hoher Dosis ebenso schädlichen Nährstoffs wie Eisen sind die hochselektive Unterscheidung und der effiziente Abbau verschiedener Substrate entscheidend. [26] Ausd iesem Grund liefern Einblicke in solche molekulare Beziehungen einen unverzichtbaren Beitrag zur Entwicklung neuer diagnostischer und therapeutischer,a ntimykotischer Verfahren. [4,7] Die genauen Wechselwirkungen zwischen hydrolytischen und reduktiven Prozessen während der Eisenfreisetzung bleiben jedoch -s elbst in den besser charakterisierten bakteriellen Systemen -w eitestgehend unklar.…”
Section: Zuschriftenunclassified
“…[4,7] Die genauen Wechselwirkungen zwischen hydrolytischen und reduktiven Prozessen während der Eisenfreisetzung bleiben jedoch -s elbst in den besser charakterisierten bakteriellen Systemen -w eitestgehend unklar. [26] Ausd iesem Grund liefern Einblicke in solche molekulare Beziehungen einen unverzichtbaren Beitrag zur Entwicklung neuer diagnostischer und therapeutischer,a ntimykotischer Verfahren. [27] Aktuelle Studien beschäftigen sich bereits mit der Anwendung von Siderophor-Konjugaten bei der Bildgebung und Bekämpfung bakterieller Krankheiten, wovon eine die intrazelluläre Siderophor-Hydrolyse durch Esterasen als fürd ie zytotoxische Aktivitätz wingend notwendig beschreibt.…”
Section: Zuschriftenunclassified
“…[25] Regarding an essential but potentially hazardous nutrient like iron, highly selective distinction between and efficient processing of different substrates is crucial. [26] Therefore,i nsights into these molecular correlations represent an essential contribution to the development of novel antifungal diagnostics and therapies. [4,7] Thep recise interplay between hydrolytic and reductive processes during iron release however still remains uncertain, even in bettercharacterized bacterial systems.…”
mentioning
confidence: 99%
“…[4,7] Thep recise interplay between hydrolytic and reductive processes during iron release however still remains uncertain, even in bettercharacterized bacterial systems. [26] Therefore,i nsights into these molecular correlations represent an essential contribution to the development of novel antifungal diagnostics and therapies. [27] Regarding bacteria, recent studies have shown the use of diverse siderophore conjugates to image and combat infections,with one describing intracellular hydrolysis by esterases as being vital for the desired cytotoxic activity.…”
mentioning
confidence: 99%